Enhancing Integrity to Strengthen Organizational Performance of Local Authorities in Malaysia - Fadzli Ahmad Tajuddin, Ahmad; Yusal Yusoff, Anis; Rezaidi Ishak, Mohd (International Journal of Engineering and Technology, 2018)
The main theme of this paper encompasses on the operationalization of the notion of integrity focusing on the performance of local authorities (LAs) in Malaysia. Specifically, the study applies the Community Integrity Building (CIB) concept which highlighted on the significant contribution of tripartite parties in gearing for better organizational performance namely community monitors, contractors and LAs. Furthermore, CIB creates an enhanced feedback loop of continuous improvement and vigilance, creating better community over time. The study also pioneered on measuring of fix rate methodology and integrity approach objectively; thus bridging the gap between conceptualization and operationalization spectrum. Finally, the paper concludes by enlightening and giving some insights on the potentials of CIB approach and changing the typical art of doing things in public service especially with regards to integrity agenda vis-â€˜a-vis building stronger local community.Â Â Â Â Â Â Â Â